2002
DOI: 10.1021/ja0285013
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal-Catalyzed Hetero-[5 + 2] Cycloadditions of Cyclopropyl Imines and Alkynes:  Dihydroazepines from Simple, Readily Available Starting Materials

Abstract: The first example of a transition metal-catalyzed hetero-[5 + 2] cycloaddition reaction is described. Use of cyclopropyl imines as five-atom components, an alkyne as a two-carbon component, and a Rh(I) catalyst enables a new route to dihydroazepines. This new hetero-[5 + 2] cycloaddition works well with aldimines, ketimines, and with substituted cyclopropanes and affords the desired dihydroazepines in excellent yields as single regioisomers. Use of serial imine formation/aza-[5 + 2] cycloaddition generates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(70 citation statements)
references
References 7 publications
1
67
0
1
Order By: Relevance
“…[33] These results reported in 2002 are illustrated in Scheme 19. In this area, Cabaleiro-Lago et al have reported a density functional theory study of these reactions.…”
Section: Intermolecular Rhodium-catalyzed [5 + 2] Cycloadditionssupporting
confidence: 56%
“…[33] These results reported in 2002 are illustrated in Scheme 19. In this area, Cabaleiro-Lago et al have reported a density functional theory study of these reactions.…”
Section: Intermolecular Rhodium-catalyzed [5 + 2] Cycloadditionssupporting
confidence: 56%
“…To our surprise, substrates bearing electronwithdrawing chloro groups, 1h and 1i, produced their products 2h and 2i in excellent isolated yields (40 and 51%; 66 and 68% based on converted C 60 ; entries 8 and 9). We isolated the monofunctionalized products 2j-l in lower chemical yields (19-22%) due to the formation of bis-and multi-addition products (entries [10][11][12]; this notion was ascribed to the presence Yield [%] [c]…”
Section: Resultsmentioning
confidence: 99%
“…[11] Intramolecular nucleophilic attack of the imine on the activated alkyne and the subsequent rearrangement forms rhodium-containing pyrrole intermediate B.…”
Section: Methodsmentioning
confidence: 99%
“…The reactions proceeded smoothly when the R 2 substituent was changed from a simple alkyl group to a benzyl, PMB, or 2-phenylethyl group to afford the desired products in moderate to good yields (Table 3, entries [1][2][3][4][5]. The substituent on the alkyne functionality could also tolerate a substituted phenyl group or thienyl, which provided the desired products in yields ranging from moderate to good (Table 3, entries [6][7][8][9][10][11]. In this reaction, irrespective of whether an electron-donating group or electron-withdrawing group was introduced on the phenyl ring, the corresponding product was obtained in a relatively low yield.…”
mentioning
confidence: 99%
See 1 more Smart Citation